A 8 years Old Girl Presented with Parry Romberg Syndrome attended at Shaheed Suhrawardy Medical College Hospital: A Case Report - Khan, Ehsanul Haque; Rashid, MA; Moonmoon, Taslima Hoq; Ahmed, Monzur; Tanim, Bidoura (Journal of Shaheed Suhrawardy Medical College, 2013)
Parry-Romberg Syndrome is an uncommon, degenerative and poorly understood condition. It is characterized by a slow and progressive atrophy affecting one side of the face. Possible factors that are involved in the pathogenesis include trauma, viral infections, heredity, endocrine disturbances and auto-immunity. Characteristically the atrophy progresses slowly for several years and soon after it become stable. In this case report, the patient of 8 years old girl complaints of gradual wasting of left side of face for 1 year involving cheek, chin, pre-auricular area, forehead, left upper lip which reveals facial asymmetry and mild wasting of left side of face as well as tongue. There was focal alopecia and depression over left side of scalp. After four months back, there was a hypopigmented area over malar prominence of same side. She was diagnosed as Parry Romberg syndrome on the basis of history, clinical examination and investigation. Antinuclear antibody and Anti-Scl-70 antibody were positive. Histopathological diagnosis was compatible with localized scleroderma. The patient was treated with drugs, physical therapy including electric stimulation as well as exercise. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14424 J Shaheed Suhrawardy Med Coll, 2012;4(2):68-71